Development of client applications on Blockchain - O. D. Okladnikova; A. V. Bukov; N. N. Zhukov (Вестник Дагестанского государственного технического университета: Технические науки, 2023)
Objective. The article discusses issues related to the process of developing client Web applications for IT projects, which are based on the principles of decentralized network technology - blockchain. The authors explore practical ways to implement the user authorization process and its interaction with the blockchain network through a client application.Method. The MetaMask browser extension was chosen as a research tool, which allows you to develop, test and run your own software modules.Result. In the course of the study, the analysis of MetaMask tools was carried out, the processes associated with the start of work were considered both from the point of view of the developer and from the point of view of the wallet user. Understanding the organization of these processes will allow users to form the necessary knowledge in the development of client applications built on blockchain.Conclusion. The program code templates developed by the authors can be used as standard ones in the development of client applications in the decentralized Ethereum network. The advantage of the proposed solutions lies in the use of simple software structures that allow the formation of basic principles.